1974
DOI: 10.1073/pnas.71.6.2453
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Regulatory Mechanisms and the Ecological Niche of Escherichia coli

Abstract: Whether the regulatory protein of an inducible operon for a catabolic pathway is a positive or a negative element in the control of expression is correlated with the frequent or infrequent presence, respectively, of the system's substrate in the natural environment.In several of the best-studied inducible operons of enteric bacteria, the regulatory protein acts as a negative (repressor) element in the control of gene expression. Examples are the galactose (1), glycerol (2), histidine utilization (3), and lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
39
0

Year Published

1979
1979
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 14 publications
1
39
0
Order By: Relevance
“…Drawing upon Savageau's demand theory of regulatory control (Savageau 1974(Savageau , 1989(Savageau , 1998, negative regulation indicates that the hut operon is infrequently used and that histidine is scarce in the natural environment of this bacterium. Indeed, the scarcity of histidine in the plant rhizosphere has previously been shown (Zhang et al 2006) and is also indicated here.…”
Section: Discussionmentioning
confidence: 99%
“…Drawing upon Savageau's demand theory of regulatory control (Savageau 1974(Savageau , 1989(Savageau , 1998, negative regulation indicates that the hut operon is infrequently used and that histidine is scarce in the natural environment of this bacterium. Indeed, the scarcity of histidine in the plant rhizosphere has previously been shown (Zhang et al 2006) and is also indicated here.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed qualitative principle calls for a quantitative theoretical formulation and analysis, as recognized already in the original work of Savageau (2). Indeed, a more recent theoretical study by Savageau (5) yielded some support for an evolutionary choice of repressors at low demand and activators at high demand.…”
mentioning
confidence: 98%
“…However, different designs can be functionally equivalent. Already 30 years ago, Savageau raised the fundamental question of whether nature's choice between functionally equivalent module designs is random or whether there is an evolutionary selection criterion (2,3). This question was posed in the context of a simple genetic switch, the elementary unit of gene regulatory modules.…”
mentioning
confidence: 99%
See 2 more Smart Citations